Related factors associated with the birth of children with Down syndrome - Farhud DD; Afrooz GA; Nosrati F (مجله دانشگاه علوم پزشکی گرگان, 2012)
Background and Objective: Down syndrome is a genetic disorder due to trisomy of 21 chromosome, which mainly is manifested by moderate to severe mental problems, including physical, sensory and motor symptoms. This study was done to determine the related factors associated with the birth of children with Down syndrome. Materials and Methods: This cross-sectional study was carried out on 913 mothers with children or fetuses of Down syndrome who were referred to genetic counseling clinics in Tehran, Iran during 2011. Diagnosis of Down syndrome confirmed by the chromosomes culture. Maternal age, maternal age at menarche, parents interfamilial marriage, maternal blood group, the number of abortions and children, collected through the questionnaires. Results: Out of 913 affected children and fetuses with Down syndrome, 420 (46%) and 493 (54%) were female and males respectively. 1.17 considered to be The male/female ratio. 32.4% of mothers were in 25-30 years of age and 42% of parants had interfamilial marriages. The abortion in mothers varied from lack of ahortion (96.7%) up to 5 repetitive abortion (0.1%). The number of children in families with affected subject consisted of 1 (15.1%), 4 (16.5%) and 11-13 (1.3%). Conclusion: This study showed that Down syndrome infants are mostly born with the mothers of 25-30 years age.